Pharyngeal swallowing in older adults: Kinematic analysis using three‐dimensional dynamic computed tomography. (14th September 2018) - Pongpipatpaiboon, Kannit; Inamoto, Yoko; Saitoh, Eiichi; Kagaya, Hitoshi; Shibata, Seiko; Aoyagi, Yoichiro; Fujii, Naoko; Palmer, Jeffrey B.; Fernández, Marlís G.
Summary: Objectives: To assess the effect of age on swallowing with a focus on structural movement, timing and duration of physiologic events. Design: Cross‐sectional study. Setting: Tertiary University Medical Center. Participants: Community‐dwelling adults (3 age groups): younger 20 to 39 (n = 23; mean 32 ± 5), middle‐aged 40 to 59 (n = 29; mean 49 ± 5) and older adults 60 to 74 (n = 15; mean 67 ± 5). Intervention: One 10‐mL honey‐thick liquid (1700 mPa) swallow was studied using 320‐row area detector computed tomography scanning. Measurements: Kinematic analysis was performed for each swallow including temporal characteristics and structural movements. Results: The duration of velopharyngeal closure and laryngeal closure (including epiglottis inversion, laryngeal vestibule closure, true vocal cord closure) was significantly different by age group ( P  =   0.002, P  <   0.001, P  =   0.017, P  =   0.041, respectively). Events were prolonged in older adults compared with middle‐aged and younger adults. The pharyngeal phase was longer for older adults. Velopharyngeal closure started earlier and continued until after complete UES opening. In younger adults, velopharyngeal and laryngeal opening occurred before complete UES opening. No differences were found in bolus movement through the oropharynx by group. Conclusion: During swallowing, older adults had a longer pharyngeal phase characterised by prolonged velopharyngeal and laryngeal closure. This difference may be a protective mechanism to compensate for age‐related weakness. A better understanding of the mechanism by which this adaptation occurs is needed to tailor rehabilitation strategies and to maintain swallowing function during the lifespan.